Protein Blotting and Detection Methods and Protocols - Kurien, Biji T.; Scofield, R. Hal.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2009)
Over the past thirty years, the development of the Western blot has revolutionized the fields of biomedical research and medical diagnostics. In Protein Blotting and Detection: Methods and Protocols, expert researchers present numerous techniques based on the Western blot, providing detailed, readily reproducible methods, tips, and alternatives directly and easily transferable to the laboratory setting. Chapters offer a large number of variations on the theme of protein transfer to solid support followed by detection, presenting adaptations of traditional techniques as well as completely original methods of protein blotting. Composed in the highly successful Methods in Molecular Biology series format, each chapter contains a brief introduction, a list of necessary materials, step-by-step methods, and a Notes section which shares tips on troubleshooting and avoiding known pitfalls. Innovative and highly practical, Protein Blotting and Detection: Methods and Protocols is an essential, hands-on guide for all investigators who hope to bring these cutting-edge procedures home to their laboratories.
Origins of Protein Blotting -- Western Blotting: Remembrance of Things Past -- to Protein Blotting -- Simultaneous Immunoblotting Analysis with Activity Gel Electrophoresis and 2-D Gel Electrophoresis -- Diffusion Blotting for Rapid Production of Multiple Identical Imprints from Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresis on a Solid Support -- Tryptic Peptide Purification Using Polyvinylidene Difluoride Membrane for Matrix-Assisted Laser Desorption Ionization Time of Flight Mass Spectrometry -- Affinity Immunoblotting for Analysis of Antibody Clonotype Distribution in a Lupus Patient Developing Anti-Ro 60 Over Time -- Nonelectrophoretic Bidirectional Transfer of a Single SDS-PAGE Gel with Multiple Antigens to Obtain 12 Immunoblots -- Slice Blotting -- Localizing Proteins by Tissue Printing -- Dot-Immunobinding Assay -- Capillary Blotting of Glycosaminoglycans on Nitrocellulose Membranes After Agarose-Gel Electrophoresis Separation -- Quantitative computerized western blotting -- Cationic electrophoresis and eastern blotting -- A miniaturized blotting system for simultaneous detecting of differentautoantibodies -- Transfer and Multiplex Immunoblotting of a Paraffin Embedded Tissue -- Multistrip Western Blotting to Increase Quantitative Data Output -- Western Blotting/Edman Sequencing using PVDF Membrane -- Blotting from PhastGel to Membranes by Ultrasound -- Ultrarapid Electrophoretic Transfer of High and Low Molecular Weight Proteins Using Heat -- Strip Immunoblotting of Multiple Antigenic Peptides to Nitrocellulose Membrane -- Affinity Purification of Autoantibodies from an Antigen Strip Excised from a Nitrocellulose Protein Blot -- Double-Blotting: A Solution to the Problem of Nonspecific Binding of Secondary Antibodies in Immunoblotting Procedures -- Efficient Electroblotting of Very Large Proteins Using a Vertical Agarose Electrophoresis System -- Semi-Dry Protein Transfer and Immunodetection of P-Selectin Using an Antibody to its C-terminal Tag -- The Multiple Antigen Blot Assay: A Simple, Versatile and Multipurpose Immunoenzymatic Technique -- Blotting from Immobilized pH Gradient Gels: Application to Total Cell Lysates -- Immunoprecipitation-Western Blot for Proteins of Low Abundance -- Native Electrophoresis and Western Blot Analysis: Method and Applications -- Grid-Immunoblotting -- Sequential Use of Immunoblots for Characterization of Autoantibody Specificities -- Renaturation of Recombinant Ro 60 Autoantigen by Calcium Ions on PVDF Membrane -- Intermittent Microwave Irradiation Facilitates Antigen-Antibody Reaction in Western Blot Analysis -- Detection of Protein-Protein Interactions by Far-Western Blotting -- On-Membrane Tryptic Digestion of Proteins for Mass Spectrometry Analysis -- Western Blot Analysis of Adhesive Interactions under Fluid Shear Conditions: The Blot Rolling Assay -- ELISPOT Assay on Membrane Microplates -- A Brief Review of Other Notable Protein Blotting Methods -- Phosphoprotein Detection on Protein Electroblot Using a Phosphate-Specific Fluorophore -- Rapid, Antibody-Free Detection of Recombinant Proteins on Blots Using Enzyme Fragment Complementation -- Fluorescent Labeling of Proteins and Its Application to SDS-PAGE and Western Blotting -- Whole and Strip Nitrocellulose Membrane as well as a New-Line-Immunoblotting ofAntigen Using the Chemiluminescence Technique -- Protein Stains to Detect Antigen on Membranes -- Use of non-radioactive detection method for North- and South-Western Blot -- Immunoblotting using Radiolabeled Reagents for Detection -- Detection of Protein Carbonyls by Means of Biotin Hydrazide-Streptavidin Affinity Methods -- (3z(BRainbow(3y (BWestern Blotting -- Multiple antigen detection (MAD) western blotting -- Detection of calcium binding by Ro 60 multiple antigenic peptides on nitrocellulose membrane using Quin-2- -- Detection of La/SS-B by Western Blot using Nanogold-Tagged Antibodies andSilver Enhancement -- Imaging Systems for Westerns: Chemiluminescence vs. Infrared Detection -- A Fluorescent Codetection System for Immunoblotting and Proteomics Through ECL-Plex and CyDye Labeling -- Visualization of Unstained Protein Bands on PVDF -- Improved Protein Detection Using Cold Microwave Technology -- TLC Blot (Far-Eastern Blot) and Its Applications -- A Brief Review of Other Notable Protein Detection Methods on Blots -- Sending Secret Messages on Nitrocellulose Membrane and the Use of a Molecular Pen for Orientation in ECL Membrane Assays.s
Keywords: Life sciences; Proteomics; Proteins; Life Sciences; Protein Science; Proteomics; Electronic books